Analysis of Phosphate Adsorption Based on Acid-base Processes - Dálnoki, Anna Boglárka; Sebők, András; Boros, Norbert; Gulyás, Miklós; Tury, Rita; Takács, Anita; Rétháti, Gabriella; Czikota, Imre; Issa, Ibrahim A. (Journal of Central European Green Innovation, 2023)
In our investigations - we developed a simple method to examine the surface ion exchange processes - where we could measure the amount of hydrogen and hydroxide ions leaving the surface of soil particles by bound phosphate ions. This type of analysis has been followed in the literature with a change in pH - which provides much less accurate results than the calculation of the surface ion balance. Soil samples were shaken with KH2PO4 solution in three replicates with P contents of 0 - 4 - 8 - 12 - 16 - 20 - 24 - 32 - 40 - 48 - 56 - 64 - 72 - 88 - and 100 mg/l. After two hours of shaking and centrifugation P content of samples was determined by photometry. The phosphorus concentration of the equilibrium solutions was used to determine the adsorption isotherm of soil phosphorus. The hydrogen ion content was determined from the separated equilibrium solutions and the original solutions used for adsorption using a high-sensitivity potentiometric titrator designed in our lab - with the addition of 0.01 M NaOH solution. The titration curves obtained for small amounts of dilute solutions - which are difficult to evaluate by other methods - were evaluated using a computer program developed in-house to determine the inflection points of the curve - i.e., the equivalence points. The missing amount of hydrogen ions from the solution was plotted as a function of the amount of phosphorus bound. Data shows that the change in the hydrogen ion content of KH2PO4 solution added to the soil - measured after equilibrium - is equal to three times the number of moles of phosphate ions bound. The slope of the fitted line was 0.35 and the correlation coefficient was 0.95. This means that each mole of phosphate bound is associated with the desorption process of three moles of OH- ions or the equivalent of three moles of H+ bound. Formally - this molar ratio expresses the binding of uncharged phosphoric acid molecules on the soil surface. Based on our measurements - several binding mechanisms for the binding of different hydrogen phosphate ions can be assumed under the given conditions. The findings indicate that some chemical reactions can be ruled out - although others could be established. During the adsorption of phosphate forms - only ion exchange reactions occur at the soil surface - which do not involve a change in surface charge - and the various hydrogen phosphate anions are exchanged for hydroxide ions.
Keywords: phosphate; adsorption isotherm; inflection point; surface-charge; ion exchange